Effective learning environments for young children using digital ressources : An Australian perspective - Downes, T.; Arthur, L.; Beecher, B. (Childhood Education Annual, 2001)
The use of digital resources in early childhood settings in Australia is a recent phenomenon. In 1999 Education.Au, a company funded by the various educational authorities in Australia, commissioned a study of the educational use of the Internet with children eight years and under. Data were collected through a literature review and discussions or interviews with all stakeholders in early childhood education: children, families, early childhood educators, school system representatives, academics, researchers, policy makers and advisers. This paper reports on the major outcome of the commissioned study: a pedagogical framework for the use of digital resources in early childhood settings. The framework includes a rationale and a description of the key elements of effective practice: quality resources, effective learning environments and appropriate teacher interactions.
Keywords: contexte d'apprentissage; contexte d'enseignement; éducation; jeunesse; lecture numérique; recherche